PEMANFAATAN CCTV SEBAGAI MEDIA PEMBINAAN KARAKTER SISWA DI SMP ISTIQOMAH SAMBAS PURBALINGGA - Syaefudin Purwanto (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
Many schools have installed CCTV but have only utilized it for security purposes and have not yet utilized it maximally for the formation and coaching of student’s characters. This type of research is a qualitative research with descriptive analysis method on the implementation of the use of CCTV as a media for the formation and coaching of student characters in Junior High School of Istiqomah Sambas Purbalingga. Data collection was carried out using interview techniques, questionnaires, observations, and document studies, while testing the validity of the data using technical triangulation and source triangulation. The results showed that (1) The establishment of discipline, order, student timeliness and security of Junior High School of Istiqomah Sambas Purbalingga increased after the installation of CCTV. (2) The effectiveness of CCTV surveillance in improving the character of Junior High School of Istiqomah Sambas Purbalingga students has been quite effective. Improvements that need to be made to maximize CCTV as a means of forming student character are inappropriate actions of students to be followed up immediately and to add CCTV monitors so that not only the Principal, Teacher BK, and Student Affairs who use CCTV as a media for monitoring but more parties who can supervise student behavior in the context of character formation.